The use of telehealth technology for lifestyle modification among patients with hypertension in Nigeria and Ghana - Chidiebere Peter Echieh; Bolade Folasade Dele-Ojo; Tijani Idris Ahmad Oseni; Paa-Kwesi Blankson; Fiifi Duodu; Bamidele O Tayo; Biodun Sulyman Alabi; Daniel F Sarpong; Mary Amoakoh-Coleman; Vincent Boima; Gbenga Ogedegbe (Digital Health, 2024)
Introduction Sedentary lifestyle and consumption of an unhealthy diet are significantly associated with hypertension in Nigeria and Ghana. Increasing the uptake of physical activity and diet rich in fruits and vegetables has been a challenge in the region. This study aimed at assessing the effect of a mobile health intervention (mhealth) on physical activity, and fruits and vegetables intake in patients with hypertension in Nigeria and Ghana Methods The study was a quasi-experimental study conducted in Mamprobi Hospital (MH) in Ghana, and State University Teaching Hospital (EKSUTH) in Nigeria. One hundred and sixteen consenting adult patients with hypertension were consecutively recruited and given regular reminders on physical activity and intake of fruits and vegetables via mobile app (mnotify ® ) for six months. All participants were followed up for six months and data collected at Baseline, three months and six months. Analysis was done using Stata 14 software (StataCorp. College Station, TX) assuming an alpha level of 0.05. Ethical approval was obtained from both countries and ethical standards were followed. Results A total of 116 (53 from Ghana and 63 from Nigeria) patients with hypertension participated in the study. Respondents had a mean age of 61.0 ± 9.1 years, and were mostly females (64.7%). There was an increase in the level of physical activity which was significant by the third month ( p  < 0.0001) but became insignificant by the 6 th month ( p  = 0.311). Fruits and vegetables intake also improved at 3 months ( p  = 0.054) and significantly at 6 months ( p  = 0.002). Conclusion The study found the use of telehealth as an effective tool for the delivery of adjunct therapy for lifestyle modification in the management of hypertension in Nigeria and Ghana. It is therefore recommended that telehealth be incorporated into the management of hypertension and other chronic diseases for better health outcome.